(untitled) (Journal of the College of Basic Education, 2022)
The interior designer is concerned with design formulations through which he discloses subjective and objective data that rise to the aesthetics of the spirit of the age and its emerging features, and in light of the transformations and changes in the overall structures and patterns of life, especially the rapid change in the field of technology that has led to a shift in the field of attention to standards of aesthetic taste to keep pace with reality that is related to collective awareness within Changing time, modern aesthetic philosophies have produced aesthetic design formulations with characteristics that correspond to the nature of the era associated with speed, mechanism, movement and the diversity of cultures, ideas and trends, seeking to form a continuous, flowing, vibrant interior space, not only to penetrate into the depths of space, but to launch into the surrounding external environment , and enriching the idea of ​​space-time, so the research problem crystallized by asking “what are the formal features on which the streamlined image is based in the design of interior spaces in a way that can secure aesthetic representations that keep pace with the language of the age”, and the research objective is to “discover the aesthetic representations of Streamline, and what are their connections and interrelationships.” Its elements and features of its formation in the design of interior spaces. The theoretical framework included two topics, the first dealt with the concept of fluidity and the aesthetics of interior design, and the second: the aesthetic representations of the fluid interior space. The research community was limited to the architectural designs (Zaha Hadid) completed during the period between (2005-2020), and the research adopted the descriptive approach to reach a set of results and conclusions, including: Energy, movement, flow, adaptation to developments, emergency response, influential forces, and interactive characteristics that refer it to a space that achieves social existence, human interdependence and environmental interdependence